Konseling Multibudaya Berbasis Nilai-Nilai Pesantren dan Spiritualitas Islam sebagai Strategi Preventif Bullying di Lingkungan Pesantren - Asna asna (Journal of Education Counseling, 2025)
The phenomenon of bullying in Islamic boarding schools is a serious challenge that requires a preventive approach based on contextual values. This article examines a multicultural counselling approach integrated with Islamic boarding school values and spirituality as a preventive strategy in addressing bullying Pesantren values such as Islamic brotherhood (ukhuwwah Islamiyah), tolerance (tasamuh), respect (ta’zim), humility (ta’wadhu’), kindness (ihsan), and trustworthiness (amanah) are identified as essential foundations for fostering healthy social interactions amidst the diverse cultural backgrounds of students. Through a multicultural counselling approach that respects differences and strengthens spiritual and moral aspects, students are guided to develop empathy, tolerance, and self-control as forms of internalising Islamic values. The study’s findings indicate that this integration not only systematically prevents bullying behaviour but also strengthens a culture of peace and religiosity within the pesantren community. This approach can serve as an alternative model for developing guidance and counselling services in multicultural boarding school-based educational institutions.